THE INFLUENCE OF EXOGENOUS GLYCINE ON GROWTH AND INTENSITY OF CYANOBACTERIA Spirulina рlatensis (Gom.) Geitl PHOTOSYNTHETIC PROCESSES - A. V. Kotinskyi; A. I. Salyuk; S. A. Zhadan (Biotechnologia Acta, 2018)
The aim of the work was to study the impact of glycine on Spirulina growth and photosynthetic processes intensity. For research the culture of Spirulina platensis (Gom.) Geitl cyanobacterium strain LGU — 603 from collection of Kholodny Institute of Botany of the National Academy of Sciences of Ukraine was used. The cultivation process was carried out in Zaruk nutrient medium in a vertical tubular apparatus of 8 cm in diameter and of volume 2 dm3 in a constant mixing of the culture medium with air.